Internalization of Maritime Cultural Values Through Education to Grow Early Childhood Awareness: a Review - Nuraeni Nuraeni; I Made Sonny Gunawan (IKIP Mataram, 2022)
Self-awareness is an aspect of personal self that is closely related to self-description, self-evaluation, self-esteem, self-regulation, self-efficacy, self-emotion, and self-recognition. Self-awareness is considered important for someone to have because it is more likely to be able to act normatively. The way that is considered effective to increase students' self-awareness is through the learning process at school. Through the learning process can make it easier for students to understand the content conveyed by the teacher. In addition, the provision of material in accordance with the theme being taught can show the quality of interaction, learning and especially the achievement of the expected individual development. In this case, what is interesting for teachers at schools to do is to be able to increase children's self-awareness from an early age about the potential they have both inside and outside themselves or their environment as capital to develop their potential. So far, early childhood education schools (PAUD) do not yet have a curriculum and operational guidelines that are prepared and implemented in accordance with regional conditions and student needs. As for minimizing these problems, it is necessary to develop a curriculum in the form of modules that are suitable for student needs and can be used by teachers as a reference in providing teaching materials. Especially in this case the module developed is intended for students who are on the Indonesian coast by internalizing Indonesian maritime culture.